THE EFFICACY OF THE INFANT FORMULA WITH PREBITOICS IN INFANTS FROM 0 TO 12 MONTHS OF AGE - N. S. Ishkova; K. S. Kaznacheev; L. F. Kaznacheeva; O. S. Bytskevich (Вопросы современной педиатрии)
The results of an open-label uncontrolled trial, assessing the tolerability and clinical efficacy of the dry milk formula «Bellakt Optimum 1» enriched with prebiotics (fructo- and galacto-oligosaccharides) are demonstrated in this article. Twenty five children at the age from 1 to 4 months were being observed. Data on medical history, physical examination, evolution of weight and height values, the results of the coproscopy and microbiological assay of faeces before the beginning of the investigation and 1 month after were used as control methods. All the patients ate the formula willingly, there were neither allergic reactions, nor signs of dyspepsia. According to the repeated examination, the amount of children with I type steatorrhea decreased from 36% to 12%; with II type steatorrhea — from 24% to 4%; with colonization of the bowels with conditionally pathogenic microorganisms — from 52% to 28%.